Applications of Built-up Sections in Lightweight Steel Trusses - Mei, C.; Ng, A.; Lau, Hieng Ho; Toh, S. (The Hong Kong Institute of Steel Construction, 2009)
Lightweight steel structures have been widely used in the construction industry. It is flexible and thus can be designed to cater for different usages. To enhance the application of cold-formed steel structures, innovative configurations are developed. These include increasing the load bearing capacity of the structure and stretching it over a larger span. Built-up section of lipped channels, either back-to-back or boxed-up for the critical elements of a truss is often adopted when it may have practical limitations in increasing the truss depth. This paper presents some of such applications in the construction industry. The built-up section possesses apparent improvement in lateral stiffness. Although these sections act together, they are currently designed individually. Current design codes do not have comprehensive provision for the design of built-up sections reflecting the improvement in design strength. The modified slenderness ratio for built-up sections in the American Iron and Steel Institute (AISI) North American Specification for the Design of Cold-Formed Steel Structural Members is adopted from researches and recommendations for hot-rolled sections. From literature search, field observation and preliminary test conducted, it reveals that the modification rule can be further developed to better reflect the improvement in the slenderness ratio of the built-up sections.